The Effectiveness of 8 Weeks Low Impact Aerobics and Yoga Combination Program on Body Fat Percentage among Obese Female (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
The prevalence of obesity of adult women in Indonesia has increased recently. Obesity among adult women will lead to health problems such as diabetes until coronary heart disease. The aim of this quasy experimental study was to determine the effectiveness of the 8-week exercise program combining low impact aerobics and yoga on the percentage of body fat in women in 2017. The subjects of this study were 12 Unesa female studentss with criteria to have Body Mass Index (BMI) obese category with age 19-24 years. The effectiveness of the 8-week low-impact exercise program of aerobics and yoga on the percentage of body fat was measured using anthropometric methods with skinfold caliper techniques measured before and after the treatment of training programs. Based on the results of calculations using t test on the percentage of body fat then 8-week exercise program combination of low impact aerobics and yoga effective in reducing body fat with an average percentage decreased of 10.56%.